Analisis Kinerja Pegawai Pada Komisi Pemilihan Umum (KPU) Kabupaten Pohuwato: Studi Evaluatif di Tengah Dinamika Konflik Sosial dan Sengketa Konstitusional Tahun 2024 - Aprilani Parengring; Hasman Umuri; Riskal Nusi (Universitas Islam Darul Ulum Lamongan, 2025)
This study presents an in-depth and comprehensive analysis of the performance of employees within the Secretariat of the General Election Commission (KPU) of Pohuwato Regency, Gorontalo Province, in welcoming and implementing a series of stages of the General Election (Pemilu) and Regional Head Election (Pilkada) in 2024. This study dissects the dimensions of work quality, quantity, timeliness, and discipline of State Civil Apparatus (ASN) and supporting staff amidst two waves of major crises (